The Impact of Working Time and Work Family Culture towards Work Family Conflict Among Career Women in Sarawak. - Sabil, Surena; Marican, Sabitha (Universiti Malaysia Sarawak, UNIMAS, 2010)
Participation of women in the workplace can be seen as a basis of excellence of future global competitiveness. In Malaysia, the women workforce comprises of 50% of the workforce and 70% of them are married working women. Hence, bringing more women into the workplace is not a choice but a necessity for both economic and global competitive. On the overall, many studies be it in the west or east has focused on the negative implication of work on family. Thus, the objective of the paper is to study the relationship of working time and work family culture towards work family conflict. The following study was conducted in Sarawak among 60 working women. The data was collected through questionnaires that were distributed personally to the respondent at their respective workplace. The findings indicated that working time and work family culture have a positive relationship towards work family conflict. Finally, the paper will discuss various ways whereby organization can promote family friendly policies at workplace in order to promote the gender equality and also women capital in Malaysia. This is because in the future the involvement of women in the workplace is even going to be at the higher rate than before.